Agents that increase AAM differentiation blunt RSV-mediated lung pathology. Issue 6 (9th July 2014) - Shirey, Kari Ann; Lai, Wendy; Pletneva, Lioubov M; Finkelman, Fred D; Feola, David J; Blanco, Jorge C G; Vogel, Stefanie N
Abstract : Therapeutic manipulation of macrophage differentiation to enhance the AAM phenotype may be a viable approach for ameliorating RSV-induced disease. Abstract: RSV is the most significant cause of serious lower respiratory tract infection in infants and young children worldwide. There is currently no vaccine for the virus, and antiviral therapy (e.g., ribavirin) has shown no efficacy against the disease. We reported that alternatively activated macrophages (AAMs) mediate resolution of RSV-induced pathology. AAM differentiation requires macrophage-derived IL-4 and -13, autocrine/paracrine signaling through the type I IL-4 receptor, and STAT6 activation. Based on these findings, we reasoned that it would be possible to intervene therapeutically in RSV disease by increasing AAM differentiation, thereby decreasing lung pathology. Mice treated with the IL-4/anti-IL-4 immune complexes, shown previously to sustain levels of circulating IL-4, increased the RSV-induced AAM markers arginase-1 and mannose receptor and decreased the lung pathology. Induction of PPARγ, shown to play a role in AAM development, by the PPARγ agonist rosiglitazone or treatment of mice with the macrolide antibiotic AZM, also reported to skew macrophage differentiation to an AAM phenotype, increased the AAM markers and mitigated RSV-induced lung pathology. Collectively, our data suggest that therapeutic manipulation of macrophage differentiation to enhance the AAM phenotype is a viable approach for ameliorating RSV-induced disease.